Break Even Point Analysis in Determining Profit in Pempek RR Pagar Dewa Business Bengkulu City - Deka Putri; Karona Cahya Susena; Herlin Herlin (Penerbit Jurnal Indonesia, 2021)
The purpose of this study was to determine the application of BEP as a profit planning tool for Pempek RR Pagar Dewa. The data collection method used is documentation, while the data analysis is qualitative and quantitative using Break Even Point (BEP) analysis. The results of the research and discussion show that the BEP in 2016 amounted to 5,902 pempek or Rp 46,896,551 with a contribution ratio of 28.8% and a business profit level of 24.26% and a margin of safety level of 84.26%. In 2017 there were 5,196 pieces of pempek or Rp 41,212,121 with a contribution ratio of 32.7% and a business profit rate of 28.5% and a margin of safety of 87.17%. And in 2018 there were 4,683 pempek items or Rp. 36,756,756 with a contribution ratio of 36.3%, a safety level or margin of safety of 89.59% and a business profit level of 32.52%. And in 2019 there were 4,622 pempek items or Rp. 36,756,756 with a contribution ratio of 36.77%, a level of security or a margin of safety of 90% and a business profit level of 33.09%.